Psikoedukasi Pencegahan Pelecehan dan Kekerasan Seksual pada Anak Usia Sekolah Dasar sebagai Upaya Preventif dan Perlindungan Dini: Pengabdian Mahasiswa KKN UNP di SDN 09 Bancah Maninjau: Penelitian - Akrobi Imana; Gilang Divianda; Syifa Urrahmah Wijaya; Sindi Rahma Ardiani; Gina Eldhini; Syifa Qolbiyah Syaiful; Yuliana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Cases of child sexual abuse and exploitation present serious challenges with lasting psychological and social consequences for victims. This study aims to assess the effectiveness of psychoeducation as an intervention strategy to improve elementary students' understanding of sexual violence prevention. Utilizing a one-group pretest-posttest design without a control group, the study involved 38 students from grades 3 to 6 at SDN 09 Bancah, Agam District. The intervention consisted of a single session featuring age-appropriate educational content, discussions, and interactive activities. Data analysis revealed a significant increase in students’ comprehension post-intervention, as indicated by the Wilcoxon test (p < 0.05) and an N-Gain score of 0.78 (classified as high). These results suggest that psychoeducation is an effective approach to enhance children’s awareness and knowledge about personal safety and sexual abuse prevention. The study highlights the need for sustained implementation of such programs in primary schools, with active involvement from teachers and parents to ensure a protective learning environment.